Prévenir l’illettrisme dès l’école primaire : analyse du cas français à la lumière de la comparaison internationale - Caroline Viriot-Goeldel (Cahiers de la Recherche sur l'Education et les Savoirs)
The use of the term “illiteracy” was consecrated in the French context by two illiteracy prevention plans put in place by the education ministers Luc Ferry (2002) and Luc Châtel (2010) respectively. Their related policies and practical application illustrate a strong political will to prevent illiteracy. Nonetheless, our comparative study reveals an insufficient degree of intervention towards early readers with reading difficulties in France in the first two years of elementary school – contributing to a certain “medicalization” of the treatment for school-age learning difficulties. And legitimately, one can raise the question of what has happened to existing RASED positions in French schools since the recent cuts. But besides the issue of resources dedicated to the treatment of learning difficulties, international comparisons shed light on how much France could benefit from adopting an approach based on strict definitions of the various stages of the intervention process, as well as a clear coordination between these stages, as seen in the intervention model adopted “en cascade” in Quebec, or the “three tiers model” pyramid strategy in the United States. Over and above the adoption of single “best practices” which experts agree would be meaningless to adopt individually, it is really a whole framework that international comparisons encourage one to consider – a process that leads from the organization of early intervention to the development of the content for reading instruction, with the goal of preventing illiteracy for generations to come.